POLA KOMUNIKASI TERAPIS GURU PADA ANAK AUTIS DI SPECIAL SCHOOL SPECTRUM - Ardan Achmad; Jordan Jeremy (Jurnal Pustaka Komunikasi, 2019)
This study aims at 1) To find out the application of therapist interpersonal communication and teachers with autistic children in Special School Spectrum; 2) To find out the obstacles faced by therapists and teachers in dealing with, directing, and teaching autistic children who aim to form independent living children; 3) To find out the reason for giving therapy that is in accordance with the abilities of each child or the level they have obtained at Special School Spectrum. The method used in this writing is descriptive qualitative approach and data collection using the interview method. Interpersonal communication of teachers and therapists to autistic children in Special School Spectrum is an example of communication with different special stages of communication in general and how these specific stages help overcome the limitations that exist in learning communication and education in autistic children. Communication between teachers and therapists for autistic children uses methods and tools that are different from communication in general.